California's Early Coverage Expansion under the Affordable Care Act: A County‐Level Analysis - Sommers, Benjamin D. (Health Serv Res, 2015)
OBJECTIVE: To assess the coverage effects of California's 2011 Low‐Income Health Program (LIHP), enacted as an “early expansion” under the Affordable Care Act (ACA), and to demonstrate the feasibility of using Census data to measure county‐level coverage changes. DATA SOURCES/STUDY SETTING: 2008–2012 American Community Survey (ACS). The sample contained California adults ages 19–64 years (n = 237,876) and children 0–18 years (n = 113,159) with incomes below 200 percent of the federal poverty level. STUDY DESIGN: Differences‐in‐differences analysis comparing public coverage, private insurance, and the uninsured rate in counties that expanded the LIHP in 2011 versus California counties not expanding during this time. Additional analyses tested for heterogeneous impacts of the LIHP and spillover effects on children. PRINCIPAL FINDINGS: Compared to nonexpansion counties, public coverage for adults increased by 1.8 percentage points (p = .02) in expanding counties, while the uninsured rate declined by 2.1 percentage points (p = .01). There was no significant change in private coverage. Public coverage gains were largest for Latinos and those with limited English proficiency. The expansion produced a positive spillover effect on children's Medicaid enrollment. CONCLUSIONS: California's 2011 expansion produced significant increases in public coverage for low‐income individuals, particularly Latinos. Substate coverage analyses with the ACS can add valuable detail to future assessments of the ACA.